Traces from a kampong: a survey of Chinese porcelain from the nineteenth and early twentieth centuries recovered from Istana Kampong Gelam - Ng, Shawn Shao-En (Nanyang Technological University, 2023)
Chinese porcelain excavated from the Istana Kampong Gelam (IKG), a Malay palace in Singapore, offers a unique opportunity to examine Chinese ceramics within a nineteenth and twentieth-century context. Although officially considered part of an early Malay settlement, historical records reveal the Istana's integration into a culturally diverse urban centre from the nineteenth century onwards, complicating the determination of its porcelain consumers. This thesis develops the first typology of Chinese porcelain from nineteenth and early-twentieth century Singapore, aimed at expanding the field of historical archaeology in Singapore. The primary goal of this typology is to identify the types of Chinese porcelain accessible to IKG's consumers. Comparative analyses involving overseas sites, including Market Street Chinatown in California and Cangdong Village in Guangdong Province, underline the potential breadth of analysis for such archaeological materials. In so doing, Chinese porcelain sherds from IKG are studied locally and within a global context, assessing resemblances and distinctions from overseas materials that may imply the extent of shared networks within the nineteenth-century porcelain industry.